EFFECTIVENESS HEEL-RAISE-LOWER EXERCISE AND DUAL TASK GAIT TRAINING AGAINST A PATIENTREVERSIBLE ISCHEMIC NEUROLOGIC DEFICIT STROKE (RIND) TO IMPROVE: A CASE STUDY - Wijayanti, Putri Eka; Rahman, Farid (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Stroke is a disease that causes damage to the brain due to infarction or blood vessels supplying blood to the brain which can cause decreased sensory function, muscle weakness, muscle atrophy, weight loss bearing, posture control, coordination, balance, and lower limb instability. Global Burden Disease data in 2010 showed that 80% of the total population had ischemic stroke while 20% had hemorrhagic stroke. While in Indonesia in 2019 the incidence of stroke per year is 200 out of 100,000 population, around 2.5% and the rest are disabled light or heavy. Purpose: The purpose of this case study is to find outEffectivenessHeel-Raise-Lower Exercise and Dual Task Gait Training for a patient Reversible Ischemic Neurologic Deficit Stroke (RIND) to improve balance. Methode: The method used in this study is Case Report. After doing therapy 3 times a week for 2 weeks The results showed an increase in each examination of muscle strength (MMT), Spasticity Examination (Aswort Scale), and Balance Check (Breg Balance Scale). Conclusin: Based on the results of the evaluation, it was concluded that in this case study, the provision of a physiotherapy intervention program in the form of: Heel-Raise-Lower Exercise and Dual Task Gait Training increase muscle strength, reduce spasticity, improve balance, coordination and walking patterns.